Economic and social perspectives of immigrant children in Germany - Frick, Joachim R. [Verfasser]; Wagner, Gert G. [Verfasser] (My University, 2001)
"Overall, children in Germany live in households with below average incomes; therefore social policies that address, the vulnerable position of Germany's children are necessary. These policies should cover targeted financial transfers as well as improvements in day care provision for children. With respect to selected non-monetary as well as monetary indicators our empirical analyses show significant differences in current living conditions between native born German children and those born to immigrants of German descent and foreign origin persons. Education is a key indicator for future economic and social perspectives. In principle, there is no formal "discrimination" of immigrant children by the German school system. However, low educational attainment levels are still being transferred from one immigrant generation to the next. The net results is that children of immigrants are not able to close the educational gap between themselves and their native German counterparts. The probable long-term consequence will be a large number of poorly qualified persons in the work force, who are much more likely to face severe labor market problems and as such will be a problem for the German economy as a whele for many years to come." (author's abstract, IAB-Doku) ((en))
Keywords: G 1.2.2.2 Soziale Sicherungssysteme; G 2.4 Sozialer Wandel; G 1 Bestand & Struktur / Statistik; G 2.4.2 Lebenskonzepte, -stile, Werte; G 1.2.3.1 Potenziale; Ausländisches Kind; Soziale Situation; Wirtschaftliche Situation; Lebensperspektive; Bildungsniveau; 1995-1996